2017
DOI: 10.1177/1040638717747322
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the diversity of astroviruses in feces from cats in Florida

Abstract: Astroviruses are small, nonenveloped RNA viruses that have been linked to numerous diseases in a variety of species, including enteric disease in humans and cheetahs. Species Mamastrovirus 2, previously known as feline astrovirus, has been isolated from the feces of domestic cats and cheetahs. A total of 122 cat fecal samples from Alachua County, FL Animal Services and the Veterinary Community Outreach Program at the University of Florida were analyzed, and 35 contained astroviral RNA that was amplified and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…In the present study, the overall apparent prevalence of FeAstV infection in domestic cats was 23.4% (46/197), which is much higher than those reported in other countries, including Australia (4.8%, 11/228) [ 16 ], the USA (10%, 5/50) [ 21 ] and south Korea (17.7%, 11/62) [ 9 ]. However, the positive rate of FeAstV in this study was similar to that reported in Florida in 2018 [ 22 ]. The differences in the prevalence of FeAstV might be related to the sample number, sampling time and tested method.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, the overall apparent prevalence of FeAstV infection in domestic cats was 23.4% (46/197), which is much higher than those reported in other countries, including Australia (4.8%, 11/228) [ 16 ], the USA (10%, 5/50) [ 21 ] and south Korea (17.7%, 11/62) [ 9 ]. However, the positive rate of FeAstV in this study was similar to that reported in Florida in 2018 [ 22 ]. The differences in the prevalence of FeAstV might be related to the sample number, sampling time and tested method.…”
Section: Discussionsupporting
confidence: 89%
“…A great deal of investigation for astrovirus worldwide indicates that not only members of the same astrovirus species can infect different host species, but also members of different astrovirus species can infect the same host. In a previous study about that astrovirus infected in cats, four types of astrovirus, one was identified as Mamastrovirus 2, one as bat astrovirus, one was similar to fox astrovirus and one as Avastrovirus, were identified in domestic cats [ 22 ]. Phylogenetic analysis based on partial RdRp gene shows that all strains identified in this study share 91.1%-97.9% nucleotide identities and 92.9%-100% amino acid identities with FeAstV reference strains, and belong to the species Mamastrovirus 2 , suggesting that Mamastrovirus 2 is most prevalent astrovirus in domestic cats.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have observed that avian astroviruses do not strictly infect avian species only. For example, Avastrovirus has been detected in diarrheic mink in China [12] and in feces from cats in Florida [8]. In addition, non-human primates can harbor a wide spectrum of mammalian and avian astroviruses [6].…”
mentioning
confidence: 99%
“…An internal control was performed on each sample to confirm for the presence of 18S (RNA) (Table ). For amplification of Astroviridae, a OneStep RT‐PCR kit (Qiagen) was used as previously described with primers shown to amplify a both genera, Avastrovirus and mamastrovirus , of Astroviridae , Astr4380F (5′GAYTGGRCNCGNTWYGATGGNA‐CIAT‐3′) and reverse primer Astr4811R (5′‐GGYTTNACCCA‐CATNCCAAA‐3′), targeting conserved regions of astrovirus ORF1b (RNA‐dependent RNA polymerase) . Bottlenose dolphin astrovirus was used as a positive control (Figure A).…”
Section: Methodsmentioning
confidence: 99%